The Effectiveness of The Website And Instagram as a Means of Promotion in Community Based Tourism Area - Chikameirani Adhanisa; Anna Fatchiya (Departemen Sains Komunikasi dan Pengembangan Masyarakat, Fakultas Ekologi Manusia, IPB, 2017)
The rise of social media users is now a great opportunity for businessmen to exploit it. Social media is often used as a means of promotion is a website and Instagram. Promotion through online media is widely used by the Manager of the tourist including community based tourism area. Online promotion is important to attracting tourists into visiting a tourist area. This research uses a quantitative approach with a survey of the methods supported by the qualitative data and followed by 171 respondents. The results of this study indicate that website and Instagram is only effective to attract attention and interest, while in attracting the desire and action is still lacking. It is influenced by the completeness of the information on the website and the completeness of information and its delivery on Instagram.Keywords : effectiveness, instagram, online promotion, website=================================================== ABSTRAK Meningkatnya pengguna media sosial saat ini menjadi peluang besar bagi pelaku bisnis . Media sosial yang sering digunakan sebagai sarana promosi adalah website dan Instagram. Promosi melalui media online banyak digunakan oleh pengelola kawasan wisata termasuk kawasan wisata berbasis masyarakat. Promosi online penting untuk menarik minat wisatawan agar mengunjungi kawasan wisata. Penelitian ini menggunakan pendekatan kuantitatif dengan metode survei yang didukung dengan data kualitatif dan diikuti oleh 171 orang responden. Hasil penelitian ini menunjukkan bahwa website dan Instagram hanya efektif untuk menarik perhatian (attention), dan menarik keingintahuan (interest), sedangkan dalam menarik keinginan (desire) dan juga tindakan (action) masih kurang. Hal tersebut dipengaruhi oleh kelengkapan informasi pada website dan kelengkapan informasi beserta tata bahasa pada Instagram Kata Kunci : efektivitas, instagram, promosi online, website